Identification of Criteria and Sub-Criteria for Urban Governance Pathology from the Perspective of Systems and Cybernetic Models: A Case Study of Hormozgan and Kerman Provinces - Kharazmi, Mahmoud; Golshani, Alireza (Digital Transformation and Administration Innovation, 2026)
The present article was conducted with the aim of identifying the factors and components of environmentally ethical technology development. In terms of purpose, the research is applied; in terms of data, it is qualitative; and in terms of implementation method, it was conducted using the systematic grounded theory approach. The statistical population consisted of key informants in the field of research within the Tehran Province Department of Environment, and interviews were conducted with 11 individuals using the snowball sampling method until theoretical saturation was achieved. Data were collected through both library research (documents and records) and field research (semi-structured interviews). To assess the validity of the research instrument, three triangulation methods were used: methodological triangulation (71%), investigator triangulation (77%), and participant triangulation (83%), indicating that the instrument had acceptable validity. Data analysis was performed using theoretical coding (based on the paradigm model of grounded theory). The coding results showed that environmentally ethical technology development consisted of 133 open codes (indicators), 26 axial codes (components), and 6 selective codes (dimensions).